Effectiveness and safety of different dosing regimens of isotretinoin for acne vulgaris: a systematic review - Lin, Linmei; Lin, Wanqi; Zheng, Yi; Cai, Huimin (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
This systematic review aimed to examine the effectiveness and safety of different isotretinoin dosing regimens for treating acne vulgaris. Isotretinoin is known as a potent treatment for moderate to severe acne, but its use is associated with dose-dependent side effects. This review aims to evaluate the comparative effectiveness of various dosing strategies, including high-dose, low-dose, and intermittent regimens. A comprehensive search of electronic databases was conducted, and 15 randomized controlled trials were included in the final analysis. The findings indicate that low-dose and intermittent dosing regimens offer comparable efficacy to high-dose regimens while minimizing adverse effects such as mucocutaneous reactions, including cheilitis and xerosis. The results highlight the potential for personalized isotretinoin therapy, which can reduce the severity of side effects while maintaining clinical effectiveness. Further research is needed to assess long-term outcomes, including relapse rates and the safety profile of these dosing regimens over extended periods. Clinicians should consider individual patient characteristics when selecting isotretinoin dosing strategies to balance therapeutic efficacy and tolerability.